Type 2 diabetes as a protein misfolding disease. Issue 7 (July 2015) - Mukherjee, Abhisek; Morales-Scheihing, Diego; Butler, Peter C.; Soto, Claudio
Highlights Accumulation of islet amyloid is present in >90% of patients with T2D. There is evidence for a role of misfolded IAPP aggregates in β-cell dysfunction. IAPP aggregates are similar to protein aggregates implicated in neurological diseases. T2D should be considered a PMD.